Evaluating User Experience (UX) on Universitas Terbuka’s Website: A Combined Survey and GTMetrix Performance Analysis - Putri, Mayang Anglingsari; Trihapningsari, Denisha; Nurdiana, Dian (Department of Informatics Engineering, 2025)
The Universitas Terbuka (UT) website serves as the primary platform for providing academic services and information to students, lecturers, and the general public. However, as the number of users and the complexity of digital services increase, User Experience (UX) becomes a crucial aspect that influences the effectiveness and user satisfaction in accessing information and utilizing available features. This study aims to evaluate and analyze the user experience of the Universitas Terbuka website using a combined approach, incorporating survey questionnaires and web performance analysis. The urgency of this research lies in the need to ensure that the UT website delivers an optimal experience for its users, particularly in terms of ease of navigation, access speed, information clarity, and responsiveness across different devices. With the growing reliance on digital systems in distance learning, UX evaluation becomes a strategic step in identifying challenges and opportunities for improvement. The novelty of this study lies in its holistic approach, which integrates subjective user feedback from surveys with objective web performance analysis. The findings of this research are expected to provide concrete recommendations for enhancing the UX quality of the Universitas Terbuka website, thereby supporting the effectiveness of distance learning and improving access to academic services.